Analysis of Efficiency of Different Distribution Channels for Select Vegetables – An Analytical Study of Telangana Region - Chakrabarti, Debopam; Desai, Kavitha (International Journal of Supply Chain Management, 2020)
The purpose of this paper is to understand the efficiency of different distribution channels for vegetable and propose a model for improvement. Efficiency is the major indicator of the supply chain performance. This analysis was part of a study to find the efficiency of different channels for vegetable supply chain and to find out what are the reasons and how farmers can get the right remuneration for their vegetables. The data was collected based on questionnaire from 410 farmers who are using different channels. The data analysis is based on the sample data for four districts of Telangana and three selected vegetables which are assumed to be representative of the overall sample frame. It was observed that there is significant variation of efficiency for different channels. There is no systematic study to understand the different contributing factors on efficiency and how it is different for different channels. This study will help in understanding the efficiency for different channel from farmer’s perspective. A framework is proposed which will help in addressing the challenges of vegetable supply chain to improve the situation for farmers by reducing the cost and losses across supply chain and also getting a better price.